Evaluación para mejorar la inyectividad en pozo para disposición final de agua en un campo petrolero utilizando inhibidores orgánicos modificados (2020)
This work is developed based on the evaluation of an organic inhibitor that seeks to increase the flow of water injected to the final disposal well C3, which brings a low injection rate due to the possible presence of substances that block the passage of the fluid to the receptor formation, recurrent event in disposal wells with some hydrocarbon load; It is necessary to verify the performance with the application of a treatment that is economical and effective, in this way to recover the properties of the rock of the formation to extend the life of the injection well. The history of the injection system of the station from January 1, 2019, the operating conditions of the well and the injection system is analyzed; Based on a bibliographic review and a composition analysis, a discussion is made about the choice of the treatment product, and the phenomena that interact to achieve the separation of the deposit that is accumulated in the middle of the system. The well test is carried out with the treatment product and the respective monitoring of the variables involved in the process, to improve injectivity. Likewise, the considerations or factors that generated the damage to the formation and the effectiveness or not of the treatment product, its composition and reactions with the aqueous medium and with the rock are evaluated.